Acute Appantisitis With Rupture of Left Ovary Corpus Luteum Cyst: Case Report - Çebi, Kibar (Fırat University, 2001)
A case related to 24 years old married women with two children is presented. She was admitted to our hospital with abdominal pain. Acute appantisitis diagnosis was made after inspection. She underwent operation. After exploration, a non-perforated acute appantisitis with hemoperiton in right lower area of abdomen and hemoragic rupture in left ovary were determined.

24 yaşında, evli, iki çocuk annesi bayan hasta ile ilgili olgu sunulmuştur. Karın ağrısı şikayeti ile müracaat etti. Yapılan muayene sonucu preoperatif tanı olarak akut apandisitis düşünüldü. Hasta ameliyata alındı. Yapılan eksplorasyonla hastada nonperfore akut apandisitis ile birlikte batın sağ alt kadranda hemoperiton ve sol overde hemorajik rüptür tespit edildi.
AKUT APANDİSİTİS İLE BİRLİKTE SOL OVER KORPUS LUTEUM KİST RÜPTÜRÜ: OLGU SUNUMU